Pola Interaksi Pengguna Platform ‘Anonymous’ Telegram terhadap Perilaku Pelecehan Seksual - Teresa Gita Olivia; Claudia Margareta; Karen Gabriella; Chontina Siahaan (CV. ULIL ALBAB CORP, 2024)
Telegram is a digital platform that facilitates social interaction and content sharing, differing from conventional social media. Primarily recognized as an instant messaging application that emphasizes privacy and security, Telegram enables users to join chat groups and exchange information. With the progression of digital technology, Telegram introduced the anonymous chatbot feature, which has gained considerable interest. The purpose of this article is to raise awareness among the public regarding the potential negative impacts of the anonymous chatbot. This article is written by exploring user communication perspectives within the symbolic interactionism theories of Herbert Mead and Herbert Blumer, specifically focusing on the anonymous Telegram channel. The writer aims to provide an understanding to anonymous Telegram users that this feature may pose threats and negative consequences, particularly concerning sexual harassment, given the prevalent digital crimes in today's era. The writer employs a literature study method as the foundation for this article. Research findings indicate that the misuse of anonymous, supported by symbols, whether in words or images, in user interactions, can trigger instances of sexual harassment.